Analysis Of The Implementation Of Cooperative Learning Make A Match With Critical Reading - Mesy Afriza Utari; Arief Muttaqiin (Department of Science Education, 2020)
This study aims to see the implementation of learning in the application of the Make A Match cooperative learning model with critical reading activities in class VII-3 of SMP N 3 Pariaman. In this study, data collection was done by filling out observation sheets. The instrument used to measure the success of the cooperative learning model makes learning fit with critical reading activities. The results of the analysis show that the application of the cooperative learning model makes the compatibility of students with critical reading activities on teacher activities by 99% with good categories and on 98% of student activities. This research proves that the cooperative learning model that is suitable for critical reading activities is appropriate.